Determining creep ratio in buried pipes for applications without pressure. Accuracy of experimental results. (February 2016) - Real, L.E. Pimentel
Abstract: A buried plastic pipe undergoes deformation, but it stabilizes at the end of a certain time not exceeding two years. Thus, there is an interest in determining the extrapolated creep of structured wall plastic pipes at 2 years. The main goal of this work is to present information regarding the assessment of results and their accuracy, based both on the requirements of the product standard [3] and on the uncertainty of the tests.